Design of a Flexible Cylindrical Antenna with Rotatable Curved Frequency Selective Surface for Omnidirectional High-Gain Applications - Hua Jing; Ge He; Shengyao Wang (International Journal of Antennas and Propagation)
In this paper, a high-gain flexible cylindrical antenna with rotatable curved frequency selective surface (FSS) is presented, which is designed for the 2.4 GHz industrial scientific medical (ISM) band. The array of 3 × 3 optimized FSS unit cells (102 × 102 mm2) is applied to improve the gain of the antenna (50.4 × 28 × 0.1 mm3). Through the rotation of the FSS, omnidirectional gain enhancement is realized. The simulation and measurement results demonstrate the feasibility of this work. The measured antenna with the FSS has omnidirectional high-gain in the operational band of 2.18–2.90 GHz, and the gain can be increased by 5.31 dBi at most. The antenna can be used in cylindrical conformal devices, and the proposed design method provides a new solution for gain enhancement of cylindrical omnidirectional antennas.